Genome organization, phylogenies, expression patterns, and three-dimensional protein models of two acetylcholinesterase genes from the red flour beetle - Lu, Yanhui; Pang, Yuan-Ping; Park, Yoonseong; Gao, Xiwu; Yao, Jianxiu; Zhang, Xin; Zhu, Kun Yan (My University, 2012)
Since the report of a paralogous acetylcholinesterase (AChE, EC3.1.1.7) gene in the greenbug (Schizaphis graminum) in 2002, two different AChE genes (Ace1 and Ace2) have been identified in each of at least 27 insect species. However, the gene models of Ace1 and Ace2, and their molecular properties have not yet been comprehensively analyzed in any insect species. In this study, we sequenced the full-length cDNAs, computationally predicted the corresponding three-dimensional protein models, and profiled developmental stage and tissue-specific expression patterns of two Ace genes from the red flour beetle (Tribolium castaneum; TcAce1 and TcAce2), a globally distributed major pest of stored grain products and an emerging model organism. TcAce1 and TcAce2 encode 648 and 604 amino acid residues, respectively, and have conserved motifs including a choline-binding site, a catalytic triad, and an acyl pocket. Phylogenetic analysis show that both TcAce genes are grouped into two insect Ace clusters and TcAce1 is completely diverged from TcAce2, suggesting that these two genes evolve from their corresponding Ace gene lineages in insect species. In addition, TcAce1 is located on chromosome 5, whereas TcAce2 is located on chromosome 2. Reverse transcription polymerase chain reaction (PCR) and quantitative realtime PCR analyses indicate that both genes are virtually transcribed in all the developmental stages and predominately expressed in the insect brain. Our computational analyses suggest that the TcAce1 protein is a robust acetylcholine (ACh) hydrolase and has susceptibility to sulfhydryl agents whereas the TcAce2 protein is not a catalytically efficient ACh hydrolase.
Citation: Lu, Y., . . . & Zhu, K. (2012). Genome Organization, Phylogenies, Expression Patterns, and Three-Dimensional Protein Models of Two Acetylcholinesterase Genes from the Red Flour Beetle. PLoS ONE, 7(2). https://doi.org/10.1371/journal.pone.0032288
Keywords: Acetylcholinesterase; Red flour beetle